2014
DOI: 10.1177/0003489414538767
|View full text |Cite
|
Sign up to set email alerts
|

The Hybrid Lid Crease Approach to Address Lateral Frontal Sinus Disease With Orbital Extension

Abstract: Objective This study aimed to describe the hybrid lid crease approach in conjunction with functional endoscopic sinus surgery (FESS) for lateral frontal sinus disease with orbital extension. Study Design Retrospective case review. Methods Patients undergoing hybrid lid crease approach with FESS for frontal sinus disease were reviewed retrospectively. Surgical indications consisted of inverting papilloma with extension into the frontal sinus (n = 1) and frontal sinus mucocele (n = 2). Inclusion criteria inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The frontal infundibulum was simultaneously opened endonasally in the sense of Draf II surgery. Complete resection of the pathology was achieved in 3/3 cases, the functional and cosmetic outcomes were described as excellent in 3/3 cases [ 128 ].…”
Section: Results Of Current Studiesmentioning
confidence: 99%
“…The frontal infundibulum was simultaneously opened endonasally in the sense of Draf II surgery. Complete resection of the pathology was achieved in 3/3 cases, the functional and cosmetic outcomes were described as excellent in 3/3 cases [ 128 ].…”
Section: Results Of Current Studiesmentioning
confidence: 99%
“…Combining the endonasal and transpalpebral orbitofrontal approaches capitalizes on the unique advantages of endonasal and open craniotomy approaches to skull base lesions. A few authors have previously reported their experience using the combined transpalpebral endonasal approach with frontal sinus disease extending laterally into the orbital and frontal sinus . In this series, we presented the utility of this combined approach in four consecutive cases with IP with extended frontal and orbital extension.…”
Section: Discussionmentioning
confidence: 96%
“…A few authors have previously reported their experience using the combined transpalpebral endonasal approach with frontal sinus disease extending laterally into the orbital and frontal sinus. 25,26 In this series, we presented the utility of this combined approach in four consecutive cases with IP with extended frontal and orbital extension. Furthermore, we illustrated how a unilateral mini-orbitocranial window can provide direct access to the entire frontal sinus on both sides to completely clear bilateral disease.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic lateralisation of the orbit can also be done for better access to the frontal sinus 13. On the other hand, for a similar far laterally located frontal sinus lesion with or without intraorbital extension, combined lid crease and endoscopic approach is relatively safer and effective technique 14 15. In broad terms, endoscopic approach can be considered safe and effective in lesions occupying the inferomedial quadrant of orbit 16.…”
Section: Discussionmentioning
confidence: 99%